2002
DOI: 10.1186/1472-6874-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term moderate exercise and increase in number of daily steps on serum lipids in women: randomised controlled trial [ISRCTN21921919]

Abstract: BackgroundThis study was designed to evaluate the effects of a 24-month period of moderate exercise on serum lipids in menopausal women.MethodsThe subjects (40–60 y) were randomly divided into an exercise group (n = 14) and a control group (n = 13). The women in the exercise group were asked to participate in a 90-minute physical education class once a week and to record their daily steps as measured by a pedometer for 24 months.ResultsMean of daily steps was significantly higher in the exercise group from abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 40 publications
3
55
0
Order By: Relevance
“…[37][38][39][40][41] These observations indicate the necessity and usefulness of step counter in the prevention and treatment of obesity and related diseases.…”
Section: Physical Activity and Obesity M Yoshioka Et Almentioning
confidence: 99%
“…[37][38][39][40][41] These observations indicate the necessity and usefulness of step counter in the prevention and treatment of obesity and related diseases.…”
Section: Physical Activity and Obesity M Yoshioka Et Almentioning
confidence: 99%
“…There were non-significant but modest differences in lipid levels at baseline, however, as the subjects were randomized by the envelope method. In a trial of menopausal women by Sugiura and co-workers, 24-month exercise training significantly increased HDL-cholesterol and significantly decreased total cholesterol and the total cholesterol/HDL-cholesterol ratio 65) . The average number of daily steps increased significantly in the exercise group after moderate exercise commenced, but remained unchanged in the control group.…”
Section: Physical Activity and Blood Lipid Levelsmentioning
confidence: 99%
“…A search for Japanese and English-language articles on RCTs investigating the effects of aerobic exercise, exercise training, exercise-based lifestyle intervention, and/or cardiac rehabilitation on lipid levels and on CVD outcomes turned up only 10 RCTs on Japanese subjects [57][58][59][60][61][62][63][64][65][66] . Three of these RCTs were excluded, however, as their lifestyle intervention programs [57][58][59] were based on multiple interventions rather than exercise.…”
Section: Physical Activity and Blood Lipid Levelsmentioning
confidence: 99%
“…A higher number of daily steps was associated with both improved high density lipoprotein (HDL) cholesterol and a significantly lower total cholesterol-to-HDL cholesterol ratio. 18 A recent study demonstrated that pedometer use was associated with a significant increase in PA and subsequent decreases in both body mass index (BMI) and blood pressure.…”
Section: Introductionmentioning
confidence: 99%